Extended DAPT Reduces Secondary Cardiovascular Events in Patients With Prior MI. Issue 28 (29th October 2015) - Zarifyan, Alla
A meta-analysis of 6 randomized trials demonstrated that when compared with aspirin therapy alone, dual antiplatelet therapy beyond 1 year decreased the risk of major adverse cardiovascular events, myocardial infarction, stroke, and cardiovascular death among high-risk patients with previous myocardial infarction while increasing the risk of major bleeding.